2018
DOI: 10.31217/p.32.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Controlling the Ship’s Path during the Turn in Confined Waterways

Abstract: One of the basic tasks in the shipping industry is to ensure safe manoeuvring and navigation through channels and confined waterways. This paper has presented a practical and theoretical approach to the assessment of safe manoeuvring in waterways based on knowledge and experience. Experienced mariners had to sail through an approach to Thorn channel in a calm weather using their own knowledge and methods to determine variable angles of rudder deflection. The navigational performance has been determined in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…However, sometimes, due to a late course change, the ship will overshoot from the track, resulting in a cross-track distance, as seen in Fig. 2 [8], [9]. As a result, a wheel over point (WOP) must be measured precisely in advance and labelled on the charted course to denote the point of change [4].…”
Section: Background Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…However, sometimes, due to a late course change, the ship will overshoot from the track, resulting in a cross-track distance, as seen in Fig. 2 [8], [9]. As a result, a wheel over point (WOP) must be measured precisely in advance and labelled on the charted course to denote the point of change [4].…”
Section: Background Of Studymentioning
confidence: 99%
“…Th e WOP may help to reduce fuel usage by optimising the vessel's voyage by keeping an optimal path [11]- [13]. Most signifi cantly, it makes a substantial contribution to the ship's navigational safety [9]. Inadequate understanding of the ship's turning capability and manoeuvrability may result in a major catastrophe [14].…”
Section: A Reminder To the Navigation Offi Cermentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of XTD at the open sea is not alarming, although shipowners may find it unpleasant as it increases fuel consumption (Reid, 1978). However, looking from the vessel-safety point of view as required by IMO (Srivastava, 2007), the XTD can be considered to be a critical aspect in navigation (Vujičić et al, 2018), as reported in a few cases where accidents happened due to ships manoeuvring off-track (Gale & Patraiko, 2007;MAIB, 2015;Steamship Mutual, 2014;TAIC, 2016). Furthermore, if navigators do not understand the fundamentals of hydrodynamics, overshooting a planned course may result in disaster.…”
Section: Introductionmentioning
confidence: 99%
“…WOP may also save fuel consumption by optimising the vessel's journey by maintaining an ideal course (Chaal, 2018;Lu et al, 2015;Reid, 1978). Most significantly, it has a substantial effect on the ship's navigational safety since failing to identify WOP was identified as one of the contributing elements to the ship's off-course manoeuvring-related disaster (Kamis et al, 2022a;Vujičić et al, 2018).…”
Section: Introductionmentioning
confidence: 99%